Classroom acoustics: Listening problems in children. Issue 1 (March 2020) - Gheller, Flavia; Lovo, Elisa; Arsie, Athena; Bovo, Roberto
The acoustic quality of classrooms is crucial for children's listening skills and consequently for their learning. Listening abilities in kids are still developing, and an environment with inadequate acoustic characteristics may create additional problems in speech perception and phonetic recognition. Background noise or reverberation may cause auditory processing problems and greater cognitive effort. There are also other elements which can make difficulty in listening and understanding in noisy environments an even more serious problem, such as learning disabilities, mild to severe hearing loss or bilingualism. Therefore, it is important to improve the acoustic quality of the classrooms, taking into account the specific needs of children in terms of signal-to-noise ratio and reverberation time, in order to ensure a proper quality of listening. The aim of this work is to analyse, through the review of previous studies, the impact that the acoustic of classrooms has on children's listening skills and learning activities.